Potentials of 3D extrusion‐based printing in resolving food processing challenges: A perspective review - Agunbiade, Adedoyin O. (2022)
Three-dimensional (3D) printing has promising application potentials in improving food product manufacturing, increasingly helping in simplifying the supply chain, as well as expanding the utilization of food materials. To further understand the current situation of 3D food printing in providing food engineering solutions with customized design, the authors checked recently conducted reviews and considered the extrusion-based type to deserve additional literature synthesis. In this perspective review, therefore, we scoped the potentials of 3D extrusion-based printing in resolving food processing challenges. The evolving trends of 3D food printing technologies, fundamentals of extrusion processes, food printer, and printing enhancement, (extrusion) food systems, algorithm development, and associated food rheological properties were discussed. The (extrusion) mechanism in 3D food printing involving some essentials for material flow and configuration, its uniqueness, suitability, and printability to food materials, (food material) types in the extrusion-based (3D food printing), together with essential food properties and their dynamics were also discussed. Additionally, some bottlenecks/concerns still applicable to extrusion-based 3D food printing were brainstormed. Developing enhanced calibrating techniques for 3D printing materials, and designing better methods of integrating data will help improve the algorithmic representations of printed foods. Rheological complexities associated with the extrusion-based 3D food printing require both industry and researchers to work together so as to tackle the (rheological) shifts that make (food) materials unsuitable.